EntoSim, a ROOT-based simulator to forecast insects' life cycle: Description and application in the case of Lobesia botrana. (March 2020) - Rossini, Luca; Severini, Maurizio; Contarini, Mario; Speranza, Stefano
Abstract: In the context of plant protection strategies against insect pests, the role of modelling is arousing interest among entomologists and environmental scientists. This work aims to provide an application of a computational tool, which includes a modified version of Von Foerster's equation to perform simulations for crop protection. More specifically, this software, named EntoSim, follows scientists and final users in each step of a simulation process. For this purpose, the program is divided into two blocks: the first contains a " laboratory phase ", in which scientists rear cohorts of insects at different constant temperatures to obtain life tables. The second block contains a simulation process and validation using field data. The developed tool was applied to the grapevine moth Lobesia botrana (Denis & Schiffermüller) alongside a 3-year validation process (2014, 2015, 2016 seasons), using data related to a monitoring activity in a vineyard located in the Castelli Romani area (Lazio, Italy). Results are a series of simulations of L. botrana life cycle, using daily average temperature as main driving variable for insect development. Comparison between simulations and field data showed a positive accordance, particularly in the 2016 season, confirming the reliability of both population dynamics model and computational tool. Highlights: A new application of the ROOT software in pest population dynamics. Description of changes and improvements on " EntoSim ". Application of a modified version of the Von Foerster's equation. Application to the case study of the European grapevine moth Lobesia botrana . Three-year validation with field data from Castelli Romani area (Lazio, Italy).